American Political Development and Comparative Democratization - King, D; Ritter, G; Whitehead, L (Johns Hopkins University Press, 2009)
American Political Development and Comparative Democratization” with Gretchen Ritter and Laurence Whitehead in Democratization in America: A Comparative Historical Analysis, Ed. Desmond King et al. Baltimore: Johns Hopkins University Press, 2009